PENGGUNAAN Trichoderma sp TERHADAP PENYAKIT KARAT PUTIH Puccinia horiana Henn PADA TANAMAN KRISAN - Frits J. Ering; Berty H. Assa; Henny V.G. Makal (Universitas Sam Ratulangi, 2022)
ABSTRACT Cultivation of horticultural crops such as ornamental chrysanthemums is a profitable business considering the excellent market potential for this plant. The main problem in chrysanthemum farming is the attack of white rust caused by a fungus (P. horiana). Trichoderma sp. is an antagonistic soil microorganism that naturally attacks pathogenic fungi and is beneficial for plants. This study aims to determine the use of Trichoderma sp against white rust that attacks chrysanthemum plants. This study was conducted using a completely randomized design (CRD) with 4 treatments and 4 replications. Based on the results of observations of symptoms of white rust disease (P. horiana) , the upper surface of the leaves is at first a yellow spot which gradually changes color to dark brown, then on the lower surface of the leaf there are pustules that are pink and gradually become dark brown. Over time it will turn white. The highest percentage of attacks was in treatment P4 (spraying) followed by P2 (watering), and P3 (watering and spraying). The conclusion that can be drawn is the use of Trichoderma sp. able to suppress white rust (P. horiana) on chrysanthemum with the best treatment in suppressing white rust (P. horiana) ie watering and spraying (P3) : 1.98% Observation data on the percentage of attacks after being tested with diversity analysis showed no significant difference between treatments. In accordance with the results of research that has been carried out, it is necessary for further research on the use of Trichoderma sp. against white rust (P. horiana) in other varieties of chrysanthemum. Keywords: Trichoderma sp, Puccinian horiana, Chrysanthemum Plants.